P117 A review of sexual health provision at coastline homeless day centre. (8th June 2017) - Sidebotham, Charlotte; Haddon, Lisa; Gates, Pam
Abstract : Introduction: Homelessness goes beyond rooflessness It is isolating and destructive. The government recognises the homeless are more vulnerable to sexual health risks and need targeted interventions. Cornwall's sexual health outreach is limited. Methods: A fortnightly afternoon drop-in sexual health clinic, run by a senior nurse and healthcare assistant, was established in a Health-for-the-Homeless (HFH) General Practice service in a socially deprived area of Cornwall. Shared-care with the HFH service whereby patients gave permission for results to be copied to the GP service. Results: Between September 2013 and January 2017, there were 498 clinic attendances, with 109 (22%) females, and 389 (78%) male clients. Of all attendances, 181 (36%) accepted sexual health screening. Of these, 17 (9.4%) were diagnosed with a sexual infection and/or hepatitis C, including 7 (3.9%) of chlamydia; 4 (2.2%) of new hepatitis C infection; 3 (1.6%) of genital warts; and 1 (0.6%) of: gonorrhoea, herpes and molluscum contagiosum. All infections were treated. 5 (5%) females had cervical cytological assessment. A 140-strong sample of notes were scrutinised to ascertain examination uptake. Of 82 indicated examinations, 26 (32%) accepted, 56 (68%) clients declined. Poor uptake may account for the low rate of skin conditions diagnosed. 20 (4%) attendances culminated in vaccination. The clinic managed 3 (0.6%) recent sexual assault cases. Discussion: Client feedback suggests that medical help would not have been sought elsewhere. Meeting in a safe environment, we believe we have broken down barriers. An increasing number of returning clients we hope reflects trust in the service. Service costing will be discussed to develop contraception provision.